De facto exchange rate regimes and currency crises: Are pegged regimes with capital account liberalization really more prone to speculative attacks? - Esaka, Taro (Journal of Banking & Finance, 2010)
This paper empirically examines whether de facto exchange rate regimes affect the occurrence of currency crises in 84 countries over the 1980–2001 period by using the probit model. We employ the de facto classification of Reinhart and Rogoff (2004) that allows us to estimate the impact of relatively long-lived exchange rate regimes on currency crises with much greater precision. We find that pegged regimes significantly decrease the likelihood of currency crises compared with floating regimes. By using the combined data of exchange rate regimes and the existence of capital controls, we also find interesting evidence that pegged regimes with capital account liberalization significantly lower the likelihood of currency crises compared with other regimes. These results are robust to a wide variety of samples and models. From the standpoint of the macroeconomic policy trilemma, we can conjecture that pegged regimes with capital account liberalization are substantially less prone to speculative attacks because they can enhance greater credibility in their currencies by abandoning monetary policy autonomy.